MoO3 facilitator enables ultrathin and stabilized Li metal anode for quasi-solid-state batteries - Zhai, Yanfang; Chen, Zongyuan; Liu, Chengyong; Ouyang, Chuying; Liang, Xiao; Paoprasert, Peerasak; Hu, Ning; Song, Shufeng (Applied physics letters, 2023)
Lithium metal is considered as a highly desirable anode for high-energy and safe quasi-solid-state batteries. Nevertheless, the terrible wettability of molten lithium does not permit it to spread out on the lithiophobic current collectors, limiting their practical applications. Herein, we report an ultrathin lithium–molybdenum (Li–Mo) composite anode to settle this hurdle by reacting molten Li with α-MoO3 nanobelts. The experimental characterizations and density functional theory calculations reveal that the interfacial binding energy between molten Li and copper (Cu) foil can be decreased by adding α-MoO3, which improves the wettability toward Cu current collector and helps to realize uniform spreading of an ultrathin Li with a thickness of ∼35 μm. As a demonstration, the ultrathin Li–Mo is stabilized to provide a high average Coulombic efficiency of ∼95.2% over 300 cycles at a high current density of 1 mA cm−2, and a capacity retention of 100% is realized for a quasi-solid-state battery paired with LiFePO4 and poly(1,3-dioxolane) electrolyte. These findings open up a promising option for enhancing the wettability of molten lithium and provide a sustainable strategy for the large-scale production of ultrathin lithium for realizing next-generation high-energy and safe quasi-solid-state batteries.